Thinking Methodically about Performance. - GREGG, BRENDAN (Communications of the ACM, 2013)
The article focuses on the complexity of systems-performance analysis and discusses methods for analyzing the computer network and operating system performance. The article discusses the blame-someone-else anti-method and the streetlight anti-method which avoid or delay the investigation of performance problems. Topics include observational bias, the problem statement, the drill-down analysis, and the workload characterization method. The USE (utilization, saturation, and errors) method identifies bottlenecks in central processing units (CPUs).